2009
DOI: 10.1037/a0017685
|View full text |Cite
|
Sign up to set email alerts
|

Discounting behavior and environmental decisions.

Abstract: Discounting plays a major role in the life cycle of environmental and natural resource policies. Evaluating centuries-scale problems like climate change with standard discount rates yields results that many find ethically unacceptable. Paradoxes abound. Low discount rates are urged for determining the net benefits of climate change, while households fail to undertake energy conservation actions that have payback periods of only a few years. Efforts to uncover discount rates from revealed and stated preferences… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(10 citation statements)
references
References 98 publications
(114 reference statements)
0
10
0
Order By: Relevance
“…Factors like low time discount rates (i.e. focusing on benefits in a longer time horizon) have been found to be associated with environmental behavior and energy consumption (Carson andRoth Tran 2009, Long et al 2018) and are also reported to be more prominent amongst highly educated people (Chao et al 2009, WhitMarsh 2011. Additional factors such as biospheric values may also mediate the effect of education if these values influence pro-environmental actions and are correlated with education (Steg 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Factors like low time discount rates (i.e. focusing on benefits in a longer time horizon) have been found to be associated with environmental behavior and energy consumption (Carson andRoth Tran 2009, Long et al 2018) and are also reported to be more prominent amongst highly educated people (Chao et al 2009, WhitMarsh 2011. Additional factors such as biospheric values may also mediate the effect of education if these values influence pro-environmental actions and are correlated with education (Steg 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Higher values of k imply greater discounting as a function of time or, in other words, a greater influence of immediacy on decision making (Green & Myerson, 2004;Kirby & Marakovic, 1995;Rachlin, Raineri, & Cross, 1991). Importantly, the propensity to discount the future occurs across many decision domains ranging from financial (e.g., Loewenstein & Thaler, 1989), health (e.g., Chapman, 2003), social (e.g., Jones & Rachlin, 2006), and environmental contexts (e.g., Carson & Tran, 2009). As such, the ubiquitous tendency to discount gains delayed in time is relevant to individual and societal functioning in many ways.…”
mentioning
confidence: 99%
“…Past 1 Since discounting plays a central role in the cost-benefit analysis of many public policies, individual discounting behavior has been studied outside of the context of energy efficiency investment also. For instance, Carson and Tran (2009) reviewed individual responses to common resource management and health risk. It is known that the similarity about discounting behavior among individuals is necessary for the success of common resource management.…”
Section: Introductionmentioning
confidence: 99%